Superkiller mutations in Saccharomyces cerevisiae suppress exclusion of M2 double-stranded RNA by L-A-HN and confer cold sensitivity in the presence of M and L-A-HN. - Ridley, S P (1984)
In an mktl host, L-A-HN double-stranded RNA excludes M2 double-stranded RNA at 30 degrees C but not at 20 degrees C. Recessive mutations suppressing the exclusion of M2 by L-A-HN in an mktl host include six ski (superkiller) genes, three of which (ski6, ski7 and ski8) are new genes. The dominant mutations in one gene (MKS50) and recessive mutations in at least two genes (mks1 and mks2) suppress M2 exclusion by L-A-HN but do not show other characteristics of ski mutations and thus define a new class of killer-related chromosomal genes. Mutations in ski2, ski3, ski4, ski6, ski7, and ski8 result in increased M copy number at 30 degrees C and prevent the cells from growing at 8 degrees C. Elimination of M double-stranded RNA from a cold-sensitive ski- strain results in the loss of cold sensitivity. ski- [KIL-sd1] strains lack L-A-HN, carry L-A-E, and have a lower M1 copy number than do ski- [KIL-k1] strains and are only slightly cold sensitive. The LTS5 (=MAK6) product is required both for low temperature growth and for M1 maintenance or replication. We propose that the elevated levels of M in ski- strains divert the host LTS5 product away from the host and to the M replication process. We also suggest that the essential role of L-A in M replication is protection of M double-stranded RNA from the negative influence of SKI+ products.